Information processing system and program - HAYASHI NOBUHIRO (2022)
This information processing system is provided with: an acquisition means for acquiring state information relating to the state of a living body and distribution information relating to the distribution of physical quantities of biomolecules; and an estimation unit that estimates a future state of the subject living body on the basis of the two-dimensional electrophoresis image of the subject living body, another two-dimensional electrophoresis image different from the two-dimensional electrophoresis image, and state information of a specific living body having the biomolecules in the distribution determined from the other two-dimensional electrophoresis image. 信息处理系统具有：获取单元，其获取与生物体的状态相关的状态信息和与生物分子的物理量的分布相关的分布信息；以及推断单元，其基于对象生物体的双向电泳图像、与该双向电泳图像不同的其他双向电泳图像以及具有根据其他双向电泳图像所确定的分布的生物分子的特定生物体的状态信息，推断对象生物体的将来的状态。